Character Formation of Students Through Physical Education: A Review of Self-Control and Cooperation at State Middle School - Moh Rifki; Siti Baitul Mukarromah; Hadi Hadi; Victoria Eka Prasetyo; Dwi Tiga Putri; Erwin Nizar Priambodo; Muhammad Yudistira Oktavian Putra; Syaherdian Juniarto Raharjo (Universitas Tadulako, 2026)
The purpose of this study is to describe the role of physical education in character building of students at SMP Negeri 19 Palu, particularly in the aspects of self-control and cooperation. This study was motivated by the gap between the ideal implementation of character education in the curriculum and learning practices in the field, which still tend to be oriented towards the development of motor aspects and have not fully integrated character values ​​optimally. The method used a quantitative approach and a cross-sectional design. Data collection was carried out after the physical education learning process had been running for one semester, thus providing an actual picture of the condition of student character. The sample consisted of students of SMP Negeri 19 Palu selected using a proportional stratified random sampling technique. The research instrument used a questionnaire to measure character indicators, particularly self-control and cooperation. The results showed that the level of student character was in the category of very poor at 10%, poor at 13%, sufficient at 43%, good at 26%, and very good at 8%. Although the